Groundwater characterization in arid regions using seismic and gravity attributes: Al Jaww Plain, UAE - Bruno, Pier Paolo G.; Vesnaver, Aldo (Frontiers in Earth Science, 2021)
This paper discusses a multivariate approach aimed to geophysical characterization of the subsurface rocks for to groundwater exploration in arid environments. We integrate several findings obtained from a single-source, single-sensor seismic profile with gravity data to detail the tectonic settings and characterize the subsurface, water-bearing formations of the Al-Jaww Plain, one of the most important groundwater reserves of United Arab Emirates. The seismic data have been acquired in in the framework of the first EAGE Middle-East Bootcamp. Edge-detection techniques applied to the Bouguer anomaly map of the Al-Jaww Plain allowed us to infer the presence of unreported ENE trending tectonic lineaments. The pre-stack depth migrated seismic image shows a clear and previously unreported east-verging thrust affecting seismic wave propagation and consistent with gravity data which was interpreted as an evidence of a detachment fold and thrust above the bottom of Fiqa Formation. Using the first-arrival picking from the common shot gathers we tested a coupled tomographic inversion of P-wave velocity and Q factor which was aimed at achieving a qualitative characterization of rock petrophysical properties. K-means clustering was used to classify and map subsurface areas characterized by similar observations of P-wave velocity and Q and therefore to outline shallow zones (<600 m) that consistent with geophysical properties that are typical for water accumulations and within the reach of water groundwater exploration.